Effect of Maternal Education, Family Income, Mother-Midwife Interface, and the Incidence of Iron Deficiency Anemia in Pemalang, Central Java - Kurniati, Ade; Astirin, Okid Parama; Suryani, Nunuk (Journal of Maternal and Child Health, 2016)
Background: Maternal mortality rate was 359 per 100,000 live birth in Indonesia in 2012. An indirect cause of maternal mortality rate is anemia. This study aimed to investigate effect of maternal education, family income, mother-midwife interface, on the incidence of iron deficiency anemia in Pemalang, Central Java.